2009
DOI: 10.1111/j.1462-2920.2009.02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel Borrelia group of tick‐borne borreliae from imported reptiles and their associated ticks

Abstract: The members of the genus Borrelia are transmitted by arthropods and known to be infectious to vertebrates. Here we found isolates and DNAs belonging to the Borrelia turcica and unknown Borrelia species from imported reptiles and their ectoparasites. The Borrelia strains were isolated from blood and multiple organs of exotic tortoises, and were experimentally infectious to captive-bred tortoises. These findings suggest that these tortoises may be a candidate as the reservoir host of the Borrelia species. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 49 publications
2
75
1
12
Order By: Relevance
“…A major omission in the study published by Adeolu and Gupta [1] is the exclusion of a Borrelia clade containing RF-like species that utilize hard ticks as vectors and reptiles as reservoir hosts [3,4].…”
mentioning
confidence: 99%
“…A major omission in the study published by Adeolu and Gupta [1] is the exclusion of a Borrelia clade containing RF-like species that utilize hard ticks as vectors and reptiles as reservoir hosts [3,4].…”
mentioning
confidence: 99%
“…2) in the Adeolu and Gupta [4] article in fact includes B. turcica, which constitutes the species from this group with a validly published name and its position was indicated to be indeterminate based on the presented results. However, in the phylogenetic tree presented by Margos et al [7], which includes B. turcica and other related reptile-associated strains of Borreliaceae without taxonomic standing, these species/strains exhibit the same pattern of branching as described by Takano et al [8], which was acknowledged by Adeolu and Gupta [4]. It should be noted, however, that in other recent studies [9,10], the position of the reptile-associated Borrelia species with respect to its branching position was found to be variable.…”
Section: Genomic Evidence For the Cohesiveness Of The Family Borreliamentioning
confidence: 92%
“…All the primer sets employed in this study and PCR conditions can be found in Table 1 [8][9][10][11][12][13][14][15]. The PCR products were electrophoresed in a 1.5% agarose gel stained with Gel-Red ™ (Biotium, Hayward, CA) and were visualized under UV light.…”
Section: Molecular Identification Of Pathogens Pcr Amplificationsmentioning
confidence: 99%